The Verticillium dahliae Spt-Ada-Gcn5 Acetyltransferase Complex Subunit Ada1 Is Essential for Conidia and Microsclerotia Production and Contributes to Virulence - Geng, Qi; Li, Huan; Wang, Dan; Sheng, Ruo-Cheng; Zhu, He; Klosterman, Steven J.; Subbarao, Krishna V.; Chen, Jie-Yin; Chen, Feng-Mao; Zhang, Dan-Dan (Frontiers in Microbiology, 2022)
Verticillium dahliae is a destructive soil-borne pathogen of many economically important dicots. The genetics of pathogenesis in V. dahliae has been extensively studied. SAGA (Spt-Ada-Gcn5 acetyltransferase complex) is an ATP-independent multifunctional chromatin remodeling complex that contributes to diverse transcriptional regulatory functions. As members of the core module in the SAGA complex in Saccharomyces cerevisiae, Ada1, together with Spt7 and Spt20, play an important role in maintaining the integrity of the complex. In this study, we identified homologs of the SAGA complex in V. dahliae and found that deletion of the Ada1 subunit (VdAda1) causes severe defects in the formation of conidia and microsclerotia, and also defects in melanin biosynthesis and virulence. The effect of VdAda1 on histone acetylation in V. dahliae was confirmed by western blot analysis. The deletion of VdAda1 resulted in genome-wide alteration of the V. dahliae transcriptome, including genes encoding transcription factors and secreted proteins, suggesting its prominent role in the regulation of transcription and virulence. Overall, we demonstrated that VdAda1, a member of SAGA complex, modulates multiple physiological processes by regulating global gene expression that impinge on its virulence and survival in V. dahliae.